Femtosecond pulsed laser-induced interconnection of single-walled carbon nanotubes. (26th July 2020) - Mei, Huanhuan; Cheng, Yang; Yin, Hailong; Wei, Fengqi; Fang, Xuyang
Abstract: With the development of electronic information technology, the fabrication of transistors based on bulk (3D) semiconductor materials has encountered bottlenecks. In view of this situation, many researchers have focused on manufacturing two-dimensional nanostructures from one-dimensional nanomaterials to apply to transistors. Based on the experimental platform of femtosecond pulsed laser irradiation system, one-dimensional single-walled carbon nanotubes (SWCNTs) deposited on silica substrate were induced to interconnect, and the optimal process parameters of the interconnection were explored. Then compared with randomly distributed SWCNTs films, the square resistance of SWCNTs films after interconnection was significantly reduced, which provided inspiration for the subsequent preparation of high-performance carbon-based thin film transistors.